Let $\{a_n\}$ be a sequence of real numbers bounded from above, $A\in \Bbb R$.

Given any $\epsilon>0$,

a)$\exists n_0 \in \Bbb N$ such that $ a_n<A+\epsilon$ for all $n\ge n_0$.

b)$\exists k\ge n_0$ such that $a_k>A-\epsilon$.

If the sequence satisfies the above two properties, show that $A=\limsup_\limits{n\to\infty}a_n$.

I know the definition of the limit superior as:$\limsup a_n = \inf_{\forall m} \sup_{n \ge m} a_n$. Also, if ($a_n$) is a real sequence bounded from above. Let $S :=$ {$t \in \Bbb R:$ $t$ is the limit of a convergent subsequence of ($a_n$) }. Then $A = sup S$. I've proved the opposite direction (i.e. Given $A=\limsup_{n\to\infty}a_n$, then it has the following two properties), but stuck on trying to prove the two properties imply A. Could someone provide a precise proof of this please? Thanks.

  • $\begingroup$ Check out the \limits I added to the title, it makes the expression look cooler. $\endgroup$ – YoTengoUnLCD Feb 4 '16 at 3:34

For any $\epsilon >0$ there exists $n_0 \in \mathbb{N}$ such that for all $n \geqslant n_0$ we have $a_n < A + \epsilon$ and $A- \epsilon < a_k$ for some $k \geqslant n_0$.


$$A - \epsilon \leqslant \sup_{n \geqslant n_0}a_n \leqslant A + \epsilon.$$

For any $m > n_0$ we have $\sup_{n \geqslant m}a_n \leqslant \sup_{n \geqslant n_0}a_n$ since $[m,\infty) \subset [n_0,\infty).$ Also there exists $k > m$ such that $A-\epsilon < a_k$.

Whence, it follows that

$$A - \epsilon \leqslant \sup_{n \geqslant m}a_n \leqslant A + \epsilon.$$

By definition, $\limsup_{n \to \infty}a_n = \inf_{m} \sup_{n \geqslant m}a_n$ and, since $\sup_{n \geqslant m}a_n$ is decreasing and bounded below, $\limsup_{n \to \infty}a_n= \lim_{m \to \infty}\sup_{n \geqslant m}a_n.$

Therefore, we have for any $\epsilon > 0$

$$A - \epsilon \leqslant \limsup_{n \to \infty}a_n \leqslant A + \epsilon.$$

Now you can reach the conclusion.

  • $\begingroup$ Can I say that hence $A-\epsilon \le lim sup a_n \le A+\epsilon$, and since $\epsilon$ is arbitrary, this can only happen if lim sup $a_n$ = $A$. $\endgroup$ – user57891 Feb 4 '16 at 3:21
  • $\begingroup$ That is the final step, but there are some intermediate steps. I can expand above if you don't see it. $\endgroup$ – RRL Feb 4 '16 at 3:24
  • $\begingroup$ If you could prove it in details that would be great, thanks! $\endgroup$ – user57891 Feb 4 '16 at 3:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.